Synergistic effect of Nb and W alloying on the microstructure and mechanical properties of CoCrFeNi high entropy alloys - Haofeng Lei; Chen Chen; Xicong Ye; Huijun Kang; Zhe Li; Junwei Fu; Tianyuan Zhang; Zhenjun Gao; Bo Li; Dong Fang; Liang Wang (Journal of Materials Research and Technology, 2024)
The strength and plasticity trade-off in metal materials can be effectively addressed by Eutectic High-Entropy Alloys (EHEAs) through the realization of heterogeneous biphase layered structures at both micrometer and nanometer scales. In this work, a series of (CoCrFeNi)88NbxW(12-x) EHEAs were prepared, and the effects of the synergistic of Nb and W elements on the microstructure and mechanical properties of CoCrFeNi High-Entropy Alloys (HEAs) were investigated. With the increase of Nb content and the decrease of W content, the microstructure of the alloy underwent three changes, from Face Center Cubic (FCC) + μ biphase to FCC + μ + Laves triple phase, and finally to FCC + Laves biphase. The strength of the alloy increases, but the compression rate decreases. Among these alloys, (CoCrFeNi)88Nb10W2 alloy exhibits exceptional mechanical properties. The synergistic effect of precipitation strengthening and grain boundary strengthening makes the yield strength, fracture strength, and plastic strain of the alloy are 1568 MPa, 2516 MPa, and 32 % respectively. In addition, in the CoCrFeNi HEAs, the weighted average atomic radius ratio (rm‾/rQ) is used to further precise the phase selection law of Laves phase and μ phase. When rm‾/rQ < 1.112, HEAs forms the μ phase, when 1.112 ≤ rm‾/rQ ≤ 1.14, HEAs forms the Laves + μ biphase, when rm‾/rQ > 1.14, HEAs forms the Laves phase. The results can provide a basis for synergistic strengthening and phase selection of CoCrFeNi HEAs.